2000
DOI: 10.1038/sj.leu.2401638
|View full text |Cite
|
Sign up to set email alerts
|

Geographic heterogeneity of cellular characteristics of acute myeloid leukemia: a comparative study of Australian and Japanese adult cases

Abstract: We assessed a large number of adults (368 from Australia and 494 from Japan) with de novo acute myeloid leukemia (AML) to define the biological differences between the two populations. In this study, AML was classified using the FrenchAmerican-British (FAB) criteria into seven groups (M1-M7). M2 was more common in Japan than in Australia, whereas M4 occurred more frequently in Australia than in Japan. Other FAB subtypes were evenly distributed. Cytogenetically, Japanese M2 displayed a higher frequency of t(8;2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
40
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 33 publications
11
40
5
Order By: Relevance
“…The frequency of aberrant karyotypes in our study was 35.6%, which was lower than the reported values for patients from the United Kingdom (UK) (52.0%, age range 44-91 years) (Grimwade et al, 2001), Hong Kong (58.0%, age range 60-89 years) (So et al, 2011), Austria (58.1%, age range 55-86 years) (Nakase et al, 2000), Japan (49.0%, age range 55-91 years) (Nakase et al, 2000), and south China (50.7%, age range 50-89 years) (Cheng et al, 2010).…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…The frequency of aberrant karyotypes in our study was 35.6%, which was lower than the reported values for patients from the United Kingdom (UK) (52.0%, age range 44-91 years) (Grimwade et al, 2001), Hong Kong (58.0%, age range 60-89 years) (So et al, 2011), Austria (58.1%, age range 55-86 years) (Nakase et al, 2000), Japan (49.0%, age range 55-91 years) (Nakase et al, 2000), and south China (50.7%, age range 50-89 years) (Cheng et al, 2010).…”
Section: Discussioncontrasting
confidence: 79%
“…Our results indicated an occurrence rate of 8.89% for t (8;21) (q22;q22), which was higher than the reported rates in the UK (2.16%) (Grimwade et al, 2001), Austria (1.16%) (Nakase et al, 2000), and Hong Kong (3.70%) (So et al, 2011), but comparable to those reported in Japan (9.50%) (Nakase et al, 2000), and south China (5.96%) (Cheng et al, 2010). Furthermore, the frequencies of -5/5q-and -7/7q-were 3.33% and 1.11%, respectively in our study, which were lower than the reported rates in the UK (12.6% and 12.6%) (Grimwade et al, 2001), but similar to those in south China (1.15% and 1.38%) (Cheng et al, 2010).…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…In most reports CD34 positivity in non-APL AML has varied between 55.8 and 69.1% [13][14][15]. We have found that HLA-DR is the single best marker for distinguishing APL from other Fig.…”
Section: Leukemia Subtypesmentioning
confidence: 54%
“…However, most of these observations were from western populations and few systematical research based on large sample sizes from Asian populations was available. The presence of geographic heterogeneity of cytogenetic abnormalities in hematological malignancies has been described (Johansson et al, 1991;Nakase et al, 2000;Chen et al, 2005), so the aim of the present study was to investigate the prevalence, feature, and specific prognostic relevance of MK in Chinese AML patients from a single center in China.…”
Section: Introductionmentioning
confidence: 99%